Crystal structure and Hirshfeld surface analysis of (E)-2-cyano-N′-(3,4,5-trimethoxybenzylidene)acetohydrazide - Subramani Uma Maheswari; Srinivasan Senthilkumar; Sivashanmugam Selvanayagam (Acta Crystallographica Section E: Crystallographic Communications)
In the title compound, C13H15N3O4, the 2-cyano-N′-methylideneacetohydrazide moiety and the trimethoxy phenol ring form a dihedral angle of 13.8 (1)°. Intermolecular N—H...O and C—H...O hydrogen bonds are observed. The intermolecular interactions were quantified and analysed using Hirshfeld surface analysis, revealing that H...H interactions contribute most to the crystal packing (38.3%).